2022
DOI: 10.24251/hicss.2022.709
|View full text |Cite
|
Sign up to set email alerts
|

Implications from Responsible Human-Robot Interaction with Anthropomorphic Service Robots for Design Science

Abstract: Accelerated by the COVID-19 pandemic, anthropomorphic service robots are continuously penetrating various domains of our daily lives. With this development, the urge for an interdisciplinary approach to responsibly design human-robot interaction (HRI), with particular attention to human dignity, privacy, compliance, and transparency, increases. This paper contributes to design science, in developing a new artifact, i.e., an interdisciplinary framework for designing responsible HRI with anthropomorphic service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…A realistic retail scenario served as experimental environment (see Fig. 1a), as service robots show a great potential to be applied here 10 . In prior research 10 , we showed the necessity to combine the expertise of the research fields of psychology, computer science, and law in the design of a responsible human-centered HRI.…”
Section: Background and Summarymentioning
confidence: 99%
See 4 more Smart Citations
“…A realistic retail scenario served as experimental environment (see Fig. 1a), as service robots show a great potential to be applied here 10 . In prior research 10 , we showed the necessity to combine the expertise of the research fields of psychology, computer science, and law in the design of a responsible human-centered HRI.…”
Section: Background and Summarymentioning
confidence: 99%
“…1a), as service robots show a great potential to be applied here 10 . In prior research 10 , we showed the necessity to combine the expertise of the research fields of psychology, computer science, and law in the design of a responsible human-centered HRI. Therefore, we implemented five conditions (neutral, transparency, liability, moral, and immoral) covering the perspectives from these three research fields.…”
Section: Background and Summarymentioning
confidence: 99%
See 3 more Smart Citations